Holy waters: an interdisciplinary examination of religion and alcohol - Lemasters, Ryan; Covell, Stephen Grover (Routledge, 2025)
"This edited volume brings together scholars from across disciplines to examine the relationship between religion and alcohol. It examines the historical, social, ritual, economic, political, and cultural relationship between religion and alcohol across time periods and around the world. Twelve chapters are tied together by two major themes: first, gender identity, and its intersection with religion and alcohol; second, identity construction in religious communities, demonstrating how alcohol can be used as a distinguishing factor for religious, ethic, and national identity. A key focus of the volume is how alcohol can bridge and divide the point at which the sacred and secular meet. With its interdisciplinary approach and engaging style, this book is an essential resource for undergraduate and graduate students in religious departments, and appeals to scholars of material culture, food, and alcohol. Additionally, the book is of interest to professionals in the alcohol industry, particularly those involved in microbrewing and winemaking, who are interested in understanding the historical and cultural contexts of their craft"--